The effects of various final irrigants on the bond strength of root dentin exposed to chloroform: An In vitro study - Feby Kuriakose; Basil Joy; Joy Mathew; Ranjith Karathodiyil; R Hariprasad; Teenu Philip (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study was to assess the reaction of different final irrigants to the bond strength of root dentin exposed to chloroform. Materials and Methods: Fifty extracted maxillary central incisors were selected. Working length was determined, and canal was instrumented with ProTaper rotary system (Dentsply Maillefer) till F4 file. The specimens were then divided into five groups (n = 10). Group 1: not disclosed to any root canal solvent, Group 2: disclosed to chloroform for 5 min, Group 3: chloroform for 5 min followed by absolute alcohol, Group 4: chloroform for 5 min followed by chlorhexidine (CHX), And Group 5 - chloroform for 5 min followed by saline. The canals were obturated with F4 gutta-percha cones with AH Plus sealer. The samples will be sectioned horizontally into 1 ± 0.1 mm thick slices. The push-out bond strength was performed in a universal testing machine. Results were statistically analyzed by one-way analysis of variance. Results: There existed a significant difference between the mean push-out bond strength of different groups. Irrigation with chloroform negatively affected the bonding between root canal sealer and root dentine. Absolute alcohol significantly improved the bond strength values. Conclusion: Exposure with chloroform during the retreatment will decrease the bonding between sealer (AH Plus) and root dentine. The use of absolute alcohol as a final irrigant improved the bonding between sealer and dentin. CHX and saline showed no improvement in bond strength.